2016
DOI: 10.1097/rli.0000000000000297
|View full text |Cite
|
Sign up to set email alerts
|

Iron(III)-Based Magnetic Resonance–Imageable Liposomal T1 Contrast Agent for Monitoring Temperature-Induced Image-Guided Drug Delivery

Abstract: Doxorubicin-loaded and Fe-SDFO-loaded TSLs displayed favorable release and stability characteristics in vitro. An in vivo proof-of-concept study showed the feasibility of monitoring drug release using the newly designed iron(III)-based CA loaded TSLs. The measured R1-contrast change correlated with the amount of doxorubicin delivered to the tumor. Moreover, the pattern of R1 change could elucidate the pattern of drug release across the tumor. This new iron(III)-based liposomal MR CA is a promising alternative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 62 publications
1
25
0
Order By: Relevance
“…All heat treatments combined with TSLs led to a significant increase in R 1 immediately after, indicating the release of contrast agent from the TSLs. For the hyperthermia and no-HIFU groups, we find a correlation between the R 1 change after hyperthermia and tumor drug concentration (R 2 = 0.43 after the second hyperthermia treatment), similar to other literature studies (32,33,56). As the R1 rhabdomyosarcoma tumor model exhibits better structured blood vessels reflected by a lower K trans and v e compared with the earlier used 9L model (34), a lower concentration of the released MRI contrast agent in the tumor is likely in the R1 rhabdomyosarcoma model.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…All heat treatments combined with TSLs led to a significant increase in R 1 immediately after, indicating the release of contrast agent from the TSLs. For the hyperthermia and no-HIFU groups, we find a correlation between the R 1 change after hyperthermia and tumor drug concentration (R 2 = 0.43 after the second hyperthermia treatment), similar to other literature studies (32,33,56). As the R1 rhabdomyosarcoma tumor model exhibits better structured blood vessels reflected by a lower K trans and v e compared with the earlier used 9L model (34), a lower concentration of the released MRI contrast agent in the tumor is likely in the R1 rhabdomyosarcoma model.…”
Section: Discussionsupporting
confidence: 90%
“…For both hyperthermia-treated animals and animals that did not receive HIFU treatment, SPECT imaging showed a relatively homogeneous uptake across the tumor, with a trend of increasing TSL concentration over 48 h. Although uptake of TSLs is a slow process with typical maximum tumor concentration reached after 8-48 h (46), the therapeutically relevant process is the intravascular release of dox from TSLs, which takes place while hyperthermia is applied, that is, within the first 40 min after injection of TSLs. Numerous preclinical studies using comparable TSL formulations have shown that hyperthermia-induced intravascular release of dox from TSLs typically led to higher tumor concentrations compared with control groups at normothermia, although strong intertumoral variations were observed depending on the tumor morphology (29,32,33,36,49). Similarly, in this study, the hyperthermia treatment led to a median tumor dox concentration of factor 14.6 higher tumor dox concentration compared with the no-HIFU group (median 2.840%ID/g vs. 0.194%ID/g) and a factor 2.9 times higher than the free doxorubicin group (median, 2.840%ID/g vs. 0.985%ID/g).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…manganese or gadolinium) with doxorubicin or co-injected particles containing contrast agents (e.g. iron) in order to assess the release and accumulation of the drug [48, 49]. Co-injection of such an imaging probe has the advantage of providing the opportunity to directly assess variations in drug concentration within a tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Co-loading of an imaging agent with a drug can influence the loading or stability of the particle and require development of a secondary formulation. Further, prolonged retention of unreleased Gd in the liver and spleen could present a translational concern [49]. Alternatively, co-injection of particles containing iron has the potential to impact temperature maps used in MRI-based procedures.…”
Section: Discussionmentioning
confidence: 99%